In vitro emergence of quinolone-resistant mutants of Escherichia coli, Enterobacter cloacae, and Serratia marcescens. - Watanabe, M (1990)
Norfloxacin- and ciprofloxacin-resistant mutants of several Enterobacter cloacae and Serratia marcescens isolates occurred at frequencies of greater than or equal to 10(-7)/CFU, which were higher than those of Escherichia coli isolates, in accordance with the increasing emergence of less-susceptible or resistant strains in clinical isolates of E. cloacae and S. marcescens.